MOTIVATION FOR THE PRACTICE OF RACE STREET (Fiep Bulletin - online, 2012)
There is a growing practice of Race Street, especially for their practicality, since it is very necessary resource material, either a great skill, only one pair of shoes appropriate, good health and willingness to run. Studies show that this activity is carried out with due care has many benefits, including: high energy expenditure, wellness, stress reduction, improved cardiorespiratory performance, reduced risk of cardiovascular diseases, among others. The reasons that lead a person to run might be: maintaining or improving quality of life, improve aesthetics, reduce stress, take pleasure in winning a contest and prizes or just compete. The aim of this study was to investigate what are the motivating factors for adherence to official competitions Road Race. For data collection we used the data sheet Psychosocial applied and validated in the "Third National Games of Youth and Motivation Questionnaire for Sports Practice of Samulski et al (1998) cited in Greco (2000), the study subjects were 29 women and 41 men aged between 15 and 68 years. Among the results, has an average age for beginning the practice of Race Street from 30 to 35 years and the average age that started competing in official events. Most individuals were encouraged by friends. It was observed that in many cases, the reasons for compliance are not the same accession and among the main reasons to start such a practice, most respondents cited improved health. As objectives and goals we have: weight loss, improved fitness and better quality of life, like that in general, most of these individuals are aware that by Road Race can have a healthier life so bio -psycho-social.
Keywords: Road Race; Motivation; Quality of Life